Practical transfusion medicine - Murphy, Michael F. [ (Michael Furber)]; Pamphilon, Derwood H. (Wiley-Blackwell, 2009)
A guide to transfusion medicine. It includes sections on alternatives to blood transfusion, and cellular and tissues therapy and organ transplantation. It also focuses on clinical aspects and covers background science and organizational issues.